2004
DOI: 10.1016/j.jacc.2004.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy: A novel adjunct to the treatment and prevention of systemic right ventricular failure

Abstract: The CRT yielded improvement in systemic RV function in patients with spontaneous or LV pacing-induced electromechanical dyssynchrony and seems to be a promising adjunct to the treatment and prevention of systemic RV failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
122
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(128 citation statements)
references
References 24 publications
2
122
1
3
Order By: Relevance
“…Some studies have shown that biventricular (BiV) pacing appears to preserve systemic ventricular function in ccTGA patients. Janousek et al initially reported the benefits of cardiac resynchronization therapy (CRT) in a small case series of 8 patients with systemic RV including ccTGA, in whom there was significant improvement in the RV fractional area change (RVFAC) as well as NYHA functional class 33. Recently, Hofferberth et al reported their evolving experience with 53 patients with ccTGA who received primary dual‐chamber UniV pacemakers.…”
Section: Management Of Conduction Disorders In Cctgamentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that biventricular (BiV) pacing appears to preserve systemic ventricular function in ccTGA patients. Janousek et al initially reported the benefits of cardiac resynchronization therapy (CRT) in a small case series of 8 patients with systemic RV including ccTGA, in whom there was significant improvement in the RV fractional area change (RVFAC) as well as NYHA functional class 33. Recently, Hofferberth et al reported their evolving experience with 53 patients with ccTGA who received primary dual‐chamber UniV pacemakers.…”
Section: Management Of Conduction Disorders In Cctgamentioning
confidence: 99%
“…However, the presence of large Thebesian veins and extensive collateralization between the RV and LV at both anterior and posterior interventricular grooves via the anterior intraventricular vein and middle cardiac vein offer alternative routes for pacing of the morphologic RV anteriorly or posteriorly 37. Alternatively, biV pacing may be performed by surgical placement of epicardial LV and RV pacing leads or with a hybrid approach that involves surgical placement of an epicardial RV pacing lead and transvenous placement of an endocardial LV lead 33, 38…”
Section: Management Of Conduction Disorders In Cctgamentioning
confidence: 99%
“…[31][32][33] Although it is not definitively clear whether it is better to pace the RV or the LV first, it is evident that nonsimultaneous pacing improves cardiac hemodynamics in the face of RV dysfunction. [31][32][33] Clinical benefits were demonstrated for patients with right heart dysfunction [34][35][36] with or without a pre-existing right bundle branch block. 34,35 For those with a right bundle branch block, pacing the RV first narrowed the QRS and improved RV dP/dt and systemic hemodynamics.…”
Section: Lv-rv Interaction and The Ivsmentioning
confidence: 99%
“…[31][32][33] Clinical benefits were demonstrated for patients with right heart dysfunction [34][35][36] with or without a pre-existing right bundle branch block. 34,35 For those with a right bundle branch block, pacing the RV first narrowed the QRS and improved RV dP/dt and systemic hemodynamics. 34,35 Importantly, the benefit of the IVS is due not only to movement but also to contractility and the overall systolic performance of the LV, which, when increased, can produce a more vigorous movement of the IVS toward the right.…”
Section: Lv-rv Interaction and The Ivsmentioning
confidence: 99%
See 1 more Smart Citation